PENGARUH STRATEGI PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP SIKAP MORAL SISWA PADA MATA PELAJARAN PKn DI SMA NNEGERI 6 PALU - Kulyawan, Roy (Katalogis, 2016)
The problem of the research; is there any difference of the moral attitude between the students taught by problem based learning strategy and expository based learning strategy, is there any difference in moral attitude of the students with cognitive model (fi) and (fd), is there any interaction between the learning strategy and cognition model towards the students’ moral attitude. The research used experimental one through 2 lines anava formula to test the main effect and interaction effect of problem based teaching strategy and expository based teaching strategy with the field independence (fi) and field dependence (fd) cognitive model on the students’ moral attitude at SMA Negeri 6 Palu. The research subject included was the first year students in two classes;20 students from class A and 20 students from class B. The analyses shows that; 1) there is no significant difference between the class taught by problem based learning strategy (0.54) and the one taught by expository based learning strategy (0.67). 2) There is no difference between the students’ moral attitude in field independence cognitive model (fi); 60% in the experimental class and 45% in the control class. Field dependence cognitive model (fd) in the experimental class is 40% and the control class is 55%. 3) There is no interaction between problem based learning strategy and expository one as well as cognitive model on the students’ moral attitude. Therefore, it can be concluded that there is no significant difference between the experimental class taught by problem based learning and the control one taught by expository based learning. There is no difference of the students’ moral attitude between the students who have field independence (fi) and field dependence (fd) cognitive model. There is no interaction between the learning strategy and the cognitive model on the students’ moral attitude in the Civics Education study at SMA Negeri 6 Palu.